TRPV1 structures in distinct conformations reveal activation mechanisms - Cao, Erhu; Liao, Maofu; Cheng, Yifan; Julius, David (Nature (London), 2013)
Transient receptor potential (TRP) channels are polymodal signal detectors that respond to a wide range of physical and chemical stimuli. Elucidating how these channels integrate and convert physiological signals into channel opening is essential to understanding how they regulate cell excitability under normal and pathophysiological conditions. Here we exploit pharmacological probes (a peptide toxin and small vanilloid agonists) to determine structures of two activated states of the capsaicin receptor, TRPV1. A domain (consisting of transmembrane segments 1–4) that moves during activation of voltage-gated channels remains stationary in TRPV1, highlighting differences in gating mechanisms for these structurally related channel superfamilies. TRPV1 opening is associated with major structural rearrangements in the outer pore, including the pore helix and selectivity filter, as well as pronounced dilation of a hydrophobic constriction at the lower gate, suggesting a dual gating mechanism. Allosteric coupling between upper and lower gates may account for rich physiological modulation exhibited by TRPV1 and other TRP channels. Using a peptide toxin and small vanilloid agonists as pharmacological probes, high-resolution electron cryo-microscopy structures of rat TRPV1–ligand complexes are solved; these structures highlight conformational differences between TRP and voltage-gated ion channels in their active states, and suggest a dual gating mechanism that may account for the ability of members of the TRP channel superfamily to integrate diverse physiological signals. Open and shut structures for a TRP ion channel Transient receptor potential (TRP) channels are sensors for a wide range of physical and chemical stimuli. In the first of a pair of related papers, Maofu Liao et al . solve the high-resolution electron cryo-microscopy structure of rat TRPV1, the receptor for capsaicin (a pungent agent from chili peppers), in a 'closed' state. The overall structure is fairly similar to that of a voltage-gated ion channel, but there are several structural features unique to TRP channels. In the second paper, Erhu Cao et al . present the structures of rat TRPV1 in the presence of a peptide neurotoxin (resiniferatoxin) and in the presence of capsaicin, yielding structures of activated states of the channel. Comparison of the closed and open structures suggests that TRPV1 has a unique two-gate mechanism of channel activation.